Application of Fermented Feed Technology to Improve Beef Cattle Business Efficiency and Student Agribusiness Learning - Khaifah Asgaf; Amriana Hifizah; Astati; Suci Ananda; Arsan Jamili; Mukhlis (Jurnal Penelitian Pendidikan IPA, 2025)
Feed costs in beef cattle farming can reach more than 60-70% of total production costs. Therefore, feed technology innovation is crucial to improve the efficiency and sustainability of livestock businesses. The objective of this study was to determine the level of adoption of fermented feed technology and how this impacts the efficiency of beef cattle farming.  The method used in this research is quantitative descriptive method. The method of determining the research area using purposive method, so that Bontonompo Subdistrict, Gowa Regency was chosen. The method of determining the sample using purposive method, with a total sample of 40 farmers as respondents. Data collection methods used were observation, interview, and questionnaire.  The results showed that the level of adoption of fermented feed technology was in the medium to high category. The use of this technology is proven to improve business efficiency, with better livestock yields and lower feed costs. The results show that the adoption of fermented feed technology has a positive and significant effect on beef cattle business efficiency. Fermented feed technology can be an alternative option to increase the productivity of beef cattle farms. This study contributes significantly to improving business efficiency in beef cattle farming through cost-effective feed strategies, while also serving as a practical learning model that enhances the entrepreneurial competence of animal husbandry students. The integration of fermented feed technology into the curriculum supports experiential learning, preparing students to apply sustainable agribusiness innovations in real-world livestock industries.